Agroforestry as Climate Change Adaptation The Case of Cocoa Farming in Ghana - Olwig, Mette Fog; Skovmand Bosselmann, Aske; Owusu, Kwadwo (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
"Cocoa-agroforestry is coming up strongly as a land use option in the humid tropics that holds the potential to reduce the severity of climate change on cocoa productivity. Reading this book inspires hope that with persistence in research, cocoa-agroforestry may hold the key for sustainability of the cocoa industry." - Boateng Kyereh, Kwame Nkrumah University of Science and Technology "Agroforestry as Climate Change Adaptation provides significant advances in understanding cocoa systems in Ghana and possible adaptations to climate change. It will have practical applications for improving the adaptation of cocoa farming in other African countries." - Jean-Paul Laclau, CIRAD "The authors give a multi-disciplinary explanation of the threats and implications of climate change, and implications of using more and different types of cocoa-agroforestry, especially diverse and different types of shade trees. The insights for policy, practice and researchmake this a must-read for anyone working on cocoa and farming systems." - Verina Ingram, Wageningen University & Research This open access book provides multidisciplinary perspectives on the potential of agroforestry to mitigate the negative impacts of climate change on cocoa production. Against the backdrop of increasingly precarious farmer livelihoods, it focuses on cocoa-agroforestry in Ghana - the second largest producer of cocoa in the world. Taking the reader on a journey across experimental plots and on-farm studies, the book delivers a holistic understanding of cocoa-agroforestry. Chapters examine historical yield and climate interactions, the effects of heat and drought on cocoa plants and the role of differing shade trees on soil fertility, yields, pests and diseases. The book discusses the socioeconomics of shade tree management, including cost-benefits, tree rights and competition for natural resources emphasizing policy implications and recommendations. Taking a multidisciplinary approach to climate-agriculture interactions, the book provides an innovative understanding of agroforestry and perennial cropping systems that goes beyond the Ghanaian cocoa belt. It is of relevance to students, researchers, farmers, practitioners and policymakers working with agroforestry and climate change adaptation. Mette Fog Olwig is Associate Professor of Global Studies and Development, Roskilde University Aske Skovmand Bosselmann is Associate Professor of Natural Resource Economics & Policy, University of Copenhagen Kwadwo Owusu is Professor of Geography and Resource Development, University of Ghana.